Gut microbiota from patients with Parkinson’s disease causes motor deficits in honeybees - Zeng, Jiaqi; Li, Yiyuan; Yan, Jingshuang; Chang, Ruqi; Xu, Mengqi; Zhou, Guanzhou; Meng, Jie; Liu, Di; Mao, Zhiqi; Yang, Yunsheng (Frontiers in Microbiology, 2024)
Objective: Parkinson's disease (PD) is possibly caused by genetic factors, environmental factors, and gut microbiota dysbiosis. This study aims to explore whether the microbiota contributes to the behavior abnormalities of PD.We transplanted gut microbiota from patients with PD or healthy controls (HC) into microbiota-free honeybees. We also established two more groups, namely the rotenone (ROT) group, in which PD-like symptoms of honeybees were induced by rotenone, and the conventional (CV) group, in which honeybees were colonized with conventional gut microbiota. The climbing assay was performed to assess the motor capabilities of honeybees. Histopathological examination was conducted to evaluate the integrity of gut mucosa. Tyrosine hydroxylase (TH) gene expression levels and dopamine (DA) concentrations in the brain were also examined. Additionally, metagenomics and full-length 16S rRNA analyses were performed to identify alterations in gut microbiota profiles, both in PD patients and honeybees.Results: Honeybees in the PD and ROT groups exhibited slower climbing speeds, downregulated TH gene expression, and impaired gut barriers. Both the HC and PD groups of honeybees successfully harbored a portion of gut microbiota from corresponding human donors, and differences in microbial composition were identified. Morganella morganii and Erysipelatoclostridium ramosum exhibited significantly increased relative abundance in the HC group, while Dorea longicatena, Collinsella aerofaciens, Lactococcus garvieae, Holdemanella biformis, Gemmiger formicilis, and Blautia obeum showed significantly increased relative abundance in the PD group. Functional predictions of microbial communities in the PD group indicated an increased synthesis of hydrogen sulfide and methane. Conclusions: A novel PD model was induced in honeybees with rotenone and gut microbiota from PD patients. This study linked PD-related behaviors to altered gut microbiota, highlighting a potential gut microbiota-brain axis involvement in PD pathogenesis. We identify previously unrecognized associations of Dorea longicatena, Collinsella aerofaciens, Lactococcus garvieae, Holdemanella biformis, Gemmiger formicilis, and Blautia obeum with PD. Additionally, pathways related to hydrogen sulfide and methane synthesis have been previously suggested as potential contributors to the development of PD, and our research further supports this hypothesis..